Is India's Long-Term Trend Growth Declining? - Ila Patnaik; Madhavi Pundit (Asian Development Bank (ADB), 2014)
The recent decline in gross domestic product (GDP) growth in India raised a debate about whether it is a trend or a business cycle slowdown. We observe a cyclical downturn post-global financial crisis due to external and domestic conditions. With global recovery strengthening and appropriate demand management policies, the business cycle downturn can be reversed. At the same time, the economy witnessed negative shocks to trend growth caused by policy uncertainty. In this paper, we argue that these shocks are temporary. A stable policy environment can give positive shocks to growth. Policy action eliminating frictions that hamper efficient allocation of resources in factor markets can be seen as a positive shock that will pull up trend growth of output. Given that the supply of factors, namely labor, human capital, infrastructure, and non-infrastructure capital appears robust and productivity growth potentially strong, timely reforms that eliminate structural bottlenecks will enable trend growth to pick up.
hdl:11540/4219
Keywords: E32; O47; 330; trend growth; business cycle; factors of production; policy shocks; India; Wirtschaftswachstum; Konjunktur; Trend; Finanzkrise; Produktionsfaktor; Wirtschaftspolitik; Schock; Indien